Modelos de compresión aplicados al proceso de densificación de combustibles sólidos binarios carbón-madera - Forero-Núñez, Carlos Andrés; Ph. D. Universidad Escuela Colombiana de Carreras Industriales Bogota (Universidad Santo Tomás. Seccional Bucaramanga, 2014)
An alternative to harness biomass resources for energy production is by producing solid biofuels. The final density and the durability of solid biofuels made of coal-sawdust mixtures vary depending upon characteristics such as the coal mass ratio in the mixture and the applied pressure.  This work aims to evaluate the applicability that existing constitutive models, obtained from biofuels based on agricultural residues, have when using binary coal-sawdust mixtures of uniform particle size at different pressures.  Unlike the Walker and Heckel model, the Kawakita  model exhibited  the  best  results  fitting a coefficient of determination R2 greater than 0.95. This model allows to analyze the different pressures that should be employed to achieve solids with final densities above 900kgm-3, improving the design stage of manufacturing systems.